2010
DOI: 10.1177/0272431610373102
|View full text |Cite
|
Sign up to set email alerts
|

Attention Problems Mediate the Association Between Severity of Physical Abuse and Aggressive Behavior in a Sample of Maltreated Early Adolescents

Abstract: Empirical evidence has accumulated documenting an association between childhood physical abuse and aggressive behavior. Relatively fewer studies have explored possible mediating mechanisms that may explain this association. The purpose of the current study was to examine whether caregiver- and youth-reported attention problems mediate the association between physical abuse severity and aggressive behavior. A sample of 240 maltreated early adolescents (ages 9–11) and their caregivers were interviewed within 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Children who were physically abused were nearly 1.5 times more likely to exhibit clinical levels of aggressive behavior at Time 1 than children who were not physically abused. The association between physical abuse and aggressive behavior in this study is consistent with previous studies that have found elevated levels of aggression among victims of maltreatment, including physical abuse [ 2 , 3 , 4 , 18 , 19 , 20 , 21 ]. An unexpected result of this study is that physical abuse was a significant predictor of aggression at Time 1 but not at Time 2.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Children who were physically abused were nearly 1.5 times more likely to exhibit clinical levels of aggressive behavior at Time 1 than children who were not physically abused. The association between physical abuse and aggressive behavior in this study is consistent with previous studies that have found elevated levels of aggression among victims of maltreatment, including physical abuse [ 2 , 3 , 4 , 18 , 19 , 20 , 21 ]. An unexpected result of this study is that physical abuse was a significant predictor of aggression at Time 1 but not at Time 2.…”
Section: Discussionsupporting
confidence: 92%
“…Physically maltreated children are at a heightened risk for developing externalizing behavior problems, including aggression and disruptive behaviors, compared with nonmaltreated children [ 2 , 4 ]. Higher levels of verbal and physical aggression in physically maltreated children compared with nonmaltreated children have consistently been reported across multiple informants, including the child self-report [ 3 ], caregivers [ 20 ], and teachers/professional raters [ 2 , 4 , 21 ]. Some studies have indicated that the association between childhood physical maltreatment and aggression remains significant even after controlling for other types of maltreatment and exposure to violence [ 18 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such knowledge in turn would aid interventions and policy formulation directed toward the well-being of children and adolescents. maltreatment has been incorporated when addressing its effects on psychopathology, in studies on childhood sexual abuse and borderline personality pathology (Zanarini et al, 2002), childhood sexual abuse and sexual problems in adulthood (Lacelle, Hebert, Lavoie, Vitaro, & Tremblay, 2012), physical abuse and aggressive and attention problems in adolescents (Garrido, Taussig, Culhane, & Raviv, 2011), and neglect and externalizing problems in children (Manly, Oshri, Lynch, Herzog, & Wortel, 2012). Each of these studies clearly indicated that an increase in severity of maltreatment was significantly related to elevated levels of psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…The presence/absence and severity of the following subtypes: Physical abuse (PA), sexual abuse (SA), neglect—failure to provide (FTP), neglect—lack of supervision (LOS), emotional maltreatment (EM), and moral, legal or educational maltreatment (MLE) were coded from file records using the Maltreatment Classification Scheme (MCS) (Barnett, Manly, & Cicchetti, ). Specifically, each notification was coded for each maltreatment subtype and the severity of the abuse/neglect using 0 to indicate absence and 1–5 to indicate severity (Garrido, Taussig, Culhane, & Raviv, ; Litrownik et al, ). Overall presence or absence of a given subtype of a particular participant reflected a coding of at least 1 across all notifications received.…”
Section: Methodsmentioning
confidence: 99%